Copy number variants in association with type 1 collagenopathy: Atypical osteogenesis imperfecta. Issue 2 (15th October 2015) - Balasubramanian, Meena; Cartwright, Ashley; Smith, Kath; Arundel, Paul; Bishop, Nicholas J.
Abstract : We report a sibling‐pair and a 4‐year old child from two families with an atypical presentation in Osteogenesis imperfecta (OI). In the sib‐pair, the older sibling initially came to medical attention due to a fracture history (Patient 1) and she was shown to have a COL1A2 mutation. In addition, she also had developmental delay, facial dysmorphism, and a history of frequent infections which led to a search for an alternate diagnosis. ArrayCGH revealed a 4.3 Mb duplication on chromosome 19q13.42q13.43, which was confirmed by FISH analysis. On further familial analysis, the younger sibling who had no previous fracture history was also found to have the COL1A2 mutation and tested positive for the 19q13.42q13.43 duplication (Patient 2). The 19q13 duplication appears to be the cause of intellectual disability in these siblings but given that this is a chromosomal duplication, it is still possible that there is an as yet unidentified cause that may account for the combined phenotype in this family. Patient 3 was a 4‐year old child presenting with a femoral fracture, blue sclerae, developmental delay, and joint hypermobility. Genetic analyses confirmed a COL1A2 mutation but also revealed an 8.8 Mb deletion of 11q24.2q25, confirmed by G‐band chromosome analysis. We discuss the differing phenotypes in patients presenting with atypical OI and stress the need to consider ancillary investigations in individuals presenting with heterogeneous phenotypic symptoms, not entirely attributable to OI. © 2015 Wiley Periodicals, Inc.